Variation in health plan specialty drug coverage: an empirical analysis. (3rd September 2019) - Margaretos, Nikoletta M.; Lai, Rachel C.; Panzer, Ari D.; Chambers, James D.
Abstract: Background: Patients' access to specialty drugs is determined in part by their health plan. Because health plans develop their own coverage policies, coverage of specialty drugs can vary, which in turn may affect their members' access to care. Aims: Our objective was to examine variation in how commercial health plans cover specialty drugs. Methods: We used the Specialty Drug Evidence and Coverage (SPEC) Database for this research. SPEC contains 6, 139 specialty drug coverage decisions current as of December 2018 issued by 17 of the largest US commercial health plans. SPEC includes 239 drugs and 484 drug-indication pairs (when a drug is approved for multiple indications, each drug-indication pair is represented separately in the database). We compared each plan's publicly available coverage policies with the drugs' FDA labels and categorized coverage as follows: (i) broader coverage than the FDA label (the plan provided coverage for populations not included in the FDA label indication), (ii) coverage with no restrictions, (iii) coverage with restrictions (the plan applies restrictions beyond the FDA label to their coverage decision, e.g., step edits or patient subgroup restrictions), (iv) mixed restrictiveness (coverage was more restrictive than the FDA label in one way but broader in another) (v), or not covered. We examined the consistency in coverage of the drug-indication pairs across the included health plans. Results: Overall, 10% of coverage decisions were broader than the FDA label, 43% covered with no restrictions, 40% covered with restrictions, 5% "mixed" restrictiveness, and 3% not covered. We found substantial variation between health plans, with the proportion of the included plans' coverage decisions including restrictions ranging from 14% to 85%. We also found notable variation in how the included health plans covered the included drug-indication pairs, with only 5% of drug-indication pairs covered the same way by all included plans. Conclusions: Health plans applied restrictions in roughly half of their coverage policies. We found notable inconsistency between plans, with the proportion of restricted coverage decisions varying widely. All plans covered few drug-indication pairs the same way, indicating that a patient’s plan may have a large influence on their access to specialty medications.